Optimization of Production Technology of KeÅŸ for Pasta - Yaman, HÃ¼lya (Indian Journal of Dairy Science, 2017)
KeÅŸ, produced by salting and drying of yoghurt, is one of the traditional dairy products common in different parts of Turkey. By the aim of reduction of the salt content, each production step of traditional process was optimized seperately and the changes during four months storage were examined.In optimization study, pH degrees of yoghurts were determined by pre-trials, rapid straining of yoghurt was carried out by centrifugator, ideal salt content were adjusted, and the most suitable drying parameters were defined respectively. According to pre-trial results, pH 4.0 x 600 revolution/90 minutes and pH 4.6 (with heating process) x 600 revolution /60 minutes were found suitable for strained yoghurt production, 3% of added salt by weight were provided the desired textural structure and 25Â°C temperature and 1.50 m/s flow rate were observed as ideal for drying. Chemical properties indicated a slight increment whereas microbiological count results displayed a small reduction during storage time. Volatile compunds profile were changed slightly during storage.Consequently salt content of KeÅŸ was decreased from 15% to 5% and the production process were decreased from 60 days to 8 days approximately compared to traditional one by changing production technology.